Emerging Strategies and Progress in the Medical Management of Marburg Virus Disease - Sanctus Musafiri; Emmanuel Edwar Siddig; John Baptist Nkuranga; Aloysius Rukundo; Tharcisse Mpunga; Augustin Sendegeya; Théogène Twagirumugabe; Ayman Ahmed; Claude Mambo Muvunyi (2025)
During the current outbreak of Marburg virus disease (MVD) in Rwanda, we synthesized evidence from the literature to improve case management. Accordingly, experimental treatment was offered to patients under close follow-up. Remdesivir alone or in combination with monoclonal antibody treatment (MBP091) complemented with supportive care has improved the clinical outcomes of patients. Additionally, we have identified several experimental therapies currently under investigation, including antiviral drugs such as favipiravir, galidesivir, obeldesivir, and remdesivir, along with monoclonal and polyclonal antibodies (e.g., polyclonal IgG, monoclonal antibody MR-78-N; MR82-N; MR191-N; monoclonal antibodies MR186-YTE and MBP091). Furthermore, substantial progress is being made in vaccine development, with promising candidates including adenovirus-vectored vaccines, DNA vaccines, and the recombinant vesicular stomatitis virus (rVSV) vaccine. Moreover, innovative preventive and treatment strategies-such as synthetic hormones like estradiol benzoate, small interfering RNA (siRNA), interferon-β therapy, and phosphorodiamidate morpholino oligomers-are emerging as potential options for MVD management. Further investment is needed to accelerate research and optimize these therapeutics and preventive modalities. Additional epidemiological, preclinical, and clinical studies are warranted to generate the evidence required to inform policymaking, resource mobilization, and the implementation of cost-effective interventions for the prevention, control, and treatment of MVD.